Diurnal Variation of Early Springtime Vertical Wind over the Tufan Dada Mountain Range of Far-Western Nepal - Regmi, Ram P. (Journal of Nepal Physical Society, 2016)
Early springtime diurnal variation of vertical wind over the 60 km long Tufan Danda mountain range located in the Far-Western Nepal has been numerically simulated with the application of WRF modeling system. Temporal and spatial distribution of vertical wind over the mountain range has been discussed up to tropospheric height. The study reveals that strong vertical wind gradient prevails throughout the troposphere of the area. The mountain wave excitations from the western edge of the mountain range appear to be propagated beyond the eastern edge of the mountain range enhancing regular bands of up- and downdrafts. The up- and downdrafts may extend beyond the tropospheric height during the late afternoon time in fair weather situations. The speed of the up- and downdrafts over the Tufan Dada may reach more than 180 cm s-1 and 200 cm s-1, respectively. High speed and great vertical extension of vertical wind over the area can significantly contribute in coupling the upper and lower atmospheric air masses and hence exchange of constituents. Tufan Danda mountain range could be one of the suitable site to monitor exchange of upper and lower atmospheric constituents. Journal of Nepal Physical Society Vol.3(1) 2015: 41-49